1977
DOI: 10.1136/jech.31.3.164
|View full text |Cite
|
Sign up to set email alerts
|

Defects of the central nervous system in Finland: I. Variations in time and space, sex distribution, and parental age.

Abstract: SUMmARY Data from the Finnish Register of Congenital Malformations for the years 1965-73 were used in a search for associations between environmental influences and defects of the central nervous system (CNS). The material consisted of 710 cases of CNS defects and their matched-pair controls. Moreover, an 'internal' control group of 259 cases of polydactyly and their matched-pair controls were used. The first report gives information on variations in time and space, sex distribution, and parental age. A higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
4
12
1
2
Order By: Relevance
“…Several authors have reported a significantly greater risk of hydro cephalus in births to older mothers [5,15,19,20,34]. However, our data, even when the approximately 26.000 Puerto Rican births are excluded, are in agreement with studies which fail to find such an association [16,17,39] and those which found no independent effect of gravidity or parity [5, 16, …”
Section: Maternal Age and Paritysupporting
confidence: 61%
See 1 more Smart Citation
“…Several authors have reported a significantly greater risk of hydro cephalus in births to older mothers [5,15,19,20,34]. However, our data, even when the approximately 26.000 Puerto Rican births are excluded, are in agreement with studies which fail to find such an association [16,17,39] and those which found no independent effect of gravidity or parity [5, 16, …”
Section: Maternal Age and Paritysupporting
confidence: 61%
“…24, 33]. Neither the present study nor others have found a significant drop in overall incidence rates since the mid-1960s [6,10,15,17,33,34,40], although modest declines similar to our own were common.…”
Section: Incidencecontrasting
confidence: 50%
“…Na Tabela 5 é feita uma comparação entre as malformações congênitas mais prevalentes neste estudo e os dados fornecidos por outros autores 10,[12][13][14] . Pode-se notar que a freqüên-cia dos tipos de malformações difere e isso se relaciona ao caráter sazonal das malformações do tubo neural e à sua etiologia multifatorial, variando de acordo com a região avaliada 15,16 .…”
Section: Discussionunclassified
“…We recorded none of such cases, although patients were offered fetal karyotyping whenever open defects were detected in ultrasonography. This may have occurred by chance, but on the other hand it is well known that the overall incidence of neural tube defects in Finland has been low (roughly 0.65 per 1,000 livebirths) before the era of prenatal screening [14]. Accordingly, in our population, the major ventral wall defects, omphalocele and gastroschisis, occur with a combined liveborn incidence of about 1 in 4,000 [15].…”
Section: Discussionmentioning
confidence: 99%